Public Trust in Productive Economic Business Capital Assistance Program in Manggalung Village - Ibrahim; Sulaiman Asang; Hasniati (Enrichment : Journal of Management, 2021)
This study aims to determine public trust in productive economic business capital assistance program in Manggalung Village, Mandalle District, Pangkep Regency, seen from the indicators of credible commitment, benevolence, honesty, competence, and fairness. The research method used is descriptive quantitative. The sample in this study amounted to 102 people. Type of data consists of primary data obtained through questionnaires, while secondary data comes from data from the Manggalung Village Office, documents and regulations related to the problem under study. The results showed that public trust in the capital assistance program for productive economy entrepreneurs in Manggalung Village was quite trusted, but there were still indicators that had not yet gained confidence, namely the indicators of honesty. This is due to the lack of socialization and transparency in budget stipulation and allocation.